Structural and Functional Abnormities of Amygdala and Prefrontal Cortex in Major Depressive Disorder With Suicide Attempts - Wang, Lifei; Zhao, Yimeng; Edmiston, Elliot K.; Womer, Fay Y.; Zhang, Ran; Zhao, Pengfei; Jiang, Xiaowei; Wu, Feng; Kong, Lingtao; Zhou, Yifang; Tang, Yanqing; Wei, Shengnan (Frontiers in Psychiatry, 2020)
Finding neural features of suicide attempts (SA) in major depressive disorder (MDD) may be helpful in preventing suicidal behavior. The ventral and medial prefrontal cortex (PFC), as well as the amygdala form a circuit implicated in emotion regulation and the pathogenesis of MDD. The aim of this study was to identify whether patients with MDD who had a history of SA show structural and functional connectivity abnormalities in the amygdala and PFC relative to MDD patients without a history of SA. We measured gray matter volume in the amygdala and PFC and amygdala-PFC functional connectivity using structural and functional magnetic resonance imaging (MRI) in 158 participants (38 MDD patients with a history of SA, 60 MDD patients without a history of SA, 60 healthy control (HC)). MDD patients with a history of SA had decreased gray matter volume in the right and left amygdala (F=30.270, P=0.000), ventral/medial/dorsal PFC (F=15.349, P=0.000), and diminished functional connectivity between the bilateral amygdala and ventral and medial PFC regions (F=22.467, P=0.000), compared with individuals who had MDD without a history of SA, and the HC group. These findings provide evidence that the amygdala and PFC may be closely related to the pathogenesis of suicidal behavior in MDD and implicate the amygdala-ventral/medial PFC circuit as a potential target for suicide intervention.